CLINICAL CHARACTERISTICS OF PATIENTS WITH MONKEYPOX INFECTION AT THEIR FIRST VISIT TO DERMATOLOGIST – A CASE SERIES - Bjekic, Milan (HEALTH CARE, 2022)
Introduction/Aim: Monkeypox disease (MPX) is caused by Monkeypox virus (MPXV) which is endemic in countries of Central and West Africa. Since May 2022 an outbreak of Monkeypox has been recorded in various regions of the world, including the Republic of Serbia. The aim of this study is to present the clinical characteristics of monkeypox cases during their first visit to a dermatologist.Case series: The study includes seven patients who consulted a dermatologist during the months of June and July 2022 due to ano-genital rash and in whom Monkeypox infection was confirmed via PCR (Polymerase chain reaction) tests. The average age of patients was 35.8 years, all were men who have sex with men, three patients were HIV-positive and the infection was transmitted through sexual intercourse. Three patients were infected abroad and four in Belgrade. In most cases incubation lasted less than a week and prodromal signs were absent. Skin lesions most frequently appeared on the penis in the form of white umbilicated papules, pustules and crusts. Serological tests for syphilis showed that none of the patients had a recent infection. Conclusion: Dermatologists should be sensitized to the presence of this disease in our country, they should suspect it early on, refer the patient to laboratory diagnostics and evaluation by an infectious disease specialist, and advise patients to isolate and abstain from sex because the disease can be transmitted during sexual intercourse.